Single-molecule DNA hybridisation studied by using a modified DNA sequencer: a comparison with surface plasmon resonance data. (29th January 2016) - Sobek, Jens; Rehrauer, Hubert; Schauer, Stefan; Fischer, David; Patrignani, Andrea; Landgraf, Stephan; Korlach, Jonas; Schlapbach, Ralph
Abstract: Current methods for the determination of molecular interactions are widely used in the analytical sciences. To identify new methods, we investigated as a model system the hybridisation of a short 7 nt oligonucleotide labelled with, structurally, very similar cyanine dyes CY3 and DY-547, respectively, to a 34 nt oligonucleotide probe immobilised in a zero-mode waveguide (ZMW) nanostructure. Using a modified commercial off-the-shelf DNA sequencer, we established the principles to measure biomolecular interactions at the single-molecule level. Kinetic data were obtained from trains of fluorescence pulses, allowing the calculation of association and dissociation rate constants ( k on, k off ). For the 7mer labelled with the positively charged CY3 dye, k on and k off are 3 larger and 2 times smaller, respectively, compared with the oligonucleotide labelled with negatively charged DY-547 dye. The effect of neighbouring molecules lacking the 7nt binding sequence on single-molecule rate constants is small. The association rate constants is reduced by only 20–35%. Hybrid dissociation is not affected, since as a consequence of the experimental design, rebinding cannot take place. Results of single-molecule experiments were compared with data obtained from surface plasmon resonance (SPR) performed under comparable conditions. A good correlation for the association rate constants within a factor of 1.5 was found. Dissociation rate constants are smaller by a factor of 2–3 which we interpreted as a result of rebinding to neighbouring probes. Results of SPR measurements tend to systematically underestimate dissociation rate constants. The amount of this deviation depends on the association rate constant and the surface probe density. As a consequence, it is recommended to work at low probe densities to keep this effect small.